1996
DOI: 10.3109/02652049609052906
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of enzyme immobilization in liposomes prepared from proliposomes

Abstract: This study investigated the influence of ionic strength, liposome net charge and enzyme concentration on the immobilization of chymotrypsin in liposomes obtained from proliposomes. Depending on ionic strength and chymotrypsin concentration, immobilization efficiencies (IE) as high as 96 and 68% were obtained for liposomes prepared with Pro-lipo 3045 S and Pro-lipo 3080 S respectively. Increasing ionic strength and enzyme concentration resulted in a decrease in IE for both types of liposomes, and this was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…In studies using charged liposomes, enzymes have been found at the surface of the liposome and appear to be active during cheese manufacture (Laloy, Vuillemard, & Simard, 1998b;Kheadr-Ehab, Vuillemard, & El-Deeb, 2000;Kheadr-Ehab, Vuillemard, & El-Deeb, 2002a, b;Kheadr-Ehab et al, 2003). Interaction of the enzyme with the liposome surface is thought to be due to hydrophobic interactions (Dufour, Vuillemard, Laloy, & Simard, 1996). The physical stability of liposomes depends upon their size, lamellarity, phospholipid structure and their method of production.…”
Section: Enzyme Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies using charged liposomes, enzymes have been found at the surface of the liposome and appear to be active during cheese manufacture (Laloy, Vuillemard, & Simard, 1998b;Kheadr-Ehab, Vuillemard, & El-Deeb, 2000;Kheadr-Ehab, Vuillemard, & El-Deeb, 2002a, b;Kheadr-Ehab et al, 2003). Interaction of the enzyme with the liposome surface is thought to be due to hydrophobic interactions (Dufour, Vuillemard, Laloy, & Simard, 1996). The physical stability of liposomes depends upon their size, lamellarity, phospholipid structure and their method of production.…”
Section: Enzyme Encapsulationmentioning
confidence: 99%
“…Typically the enzymes are added in this aqueous phase and mixed to form MLVs. Enzymes encapsulation efficiencies of 96% (Dufour et al, 1996) have been achieved with curd entrapment levels of 64% (Laloy, Vuillemard, El-Abboudi, Fliss, & DeGrace, 1996b).…”
Section: Enzyme Encapsulationmentioning
confidence: 99%
“…Recently, liposome, spherical particles with sizes at the range of the nanometer to micrometer formed by polar lipids (Charcosset 2009;Taylor et al 2005) has received special attention in the literature (Mozafari et al 2008a, b). Liposome technology has generated much interest in food industry for the encapsulation of different materials such as ferrous glycinate (Ding et al 2011), ferrous sulfate (Xia and Xu 2005), antioxidant (Mozafari et al 2006), nisin (Taylor et al 2007;Laridi et al 2003;Colas et al 2007) β-galactosidase (Rao et al 1994) and different cheese accelerated enzymes such as lipase (Kheadr et al 2002), Nutrease (Alkhalaf et al 1989), chymotripsine (Laloy et al 1998;Dufour et al 1996), chymosine (Picon et al 1994), neutral protease (Picon et al 1995), cyprosine (Picon et al 1996) bacterial and fungal protease, Flavourzyme and palatase . Different methods such as reverse-phase evaporation, dehydration-rehydration, microfludization technique and proliposome usage have been applied for liposome manufacturing with a variation of EE (%) ranging from 10 to 40.3 %.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods such as reverse-phase evaporation, dehydration-rehydration, microfludization technique and proliposome usage have been applied for liposome manufacturing with a variation of EE (%) ranging from 10 to 40.3 %. However, most of the methods (except microfluidization technique and proliposome usage) require organic solvent causing enzyme inactivation (Rao et al 1994) which make them unsuitable for food products (Skeie 1994;Dufour et al 1996). The disadvantages of the microfluidization technique are loss of material, contamination, relatively difficult for scaling up and the employment of very high shearing forces that can potentially damage the structure of the compounds to be encapsulated (Maa and Hsu 1999;Kasaai et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation